2019
DOI: 10.1111/jcpp.13161
|View full text |Cite
|
Sign up to set email alerts
|

From man to fly – convergent evidence links FBXO25 to ADHD and comorbid psychiatric phenotypes

Abstract: Background: Mental disorders, including Attention-Deficit/Hyperactivity Disorder (ADHD), have a complex etiology, and identification of underlying genetic risk factors is challenging. This study used a multistep approach to identify and validate a novel risk gene for ADHD and psychiatric comorbidity. Methods: In a single family, severely affected by ADHD and cooccurring disorders, we applied single nucleotide polymorphism (SNP)-array analysis to detect copynumber variations (CNVs) linked to disease. Genes pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Beyond those involved in the actually restricted candidate region, other genes less frequently included in 8p23.2-pter microdeletions may cooperate to the clinical spectrum. Examples are CSMD1 in 8p23.2, a dosage-sensitive gene associated to ASD, schizophrenia and epilepsy [ 68 , 69 , 70 ] and FBXO25, recently associated to neuropsychiatric disorders [ 71 ]. Both genes are not included in most of the microdeletions reported to date, but they might act as phenotypic modifiers in patients with microdeletions spanning until the 8p23.2 or 8p23.3 regions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond those involved in the actually restricted candidate region, other genes less frequently included in 8p23.2-pter microdeletions may cooperate to the clinical spectrum. Examples are CSMD1 in 8p23.2, a dosage-sensitive gene associated to ASD, schizophrenia and epilepsy [ 68 , 69 , 70 ] and FBXO25, recently associated to neuropsychiatric disorders [ 71 ]. Both genes are not included in most of the microdeletions reported to date, but they might act as phenotypic modifiers in patients with microdeletions spanning until the 8p23.2 or 8p23.3 regions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Combining all this information, it is possible to speculate that the protein has biological effects other than regulating spermatogenesis. At this regard, a very interesting study has recently shown that Tdrp is linked to mental disorders, including Attention-Deficit/Hyperactivity Disorder (ADHD) (Harich et al, 2019). The authors sought to validate the relevance of their finding in Drosophila but while they could find two orthologues for FBXO25, there was no orthologue for Tdrp.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling plays a role in different psychiatric disorders, including ADHD and autism (Poelmans et al, 2013;Vithayathil et al, 2018). Moreover, the brain relies on ubiquitination to finetune protein content in order to react to new stimuli (Hegde & van Leeuwen, 2017). Another E3 ligase, FBXO33, has been the top-finding of the first casecontrol genome-wide association study of persistent ADHD (Sanchez-Mora et al, 2015).…”
Section: Discussionmentioning
confidence: 99%